THE ROLE OF MANAGERIAL ABILITY AND PRODUCT DIFFERENTIATION ON THE PERFORMANCE OF MSMES IN BATAM CITY - Hendri Herman; Suyono Suyono (Jurnal Apresiasi Ekonomi, 2024)
The MSME sector, which is proven to be able to absorb a large number of workers, is also a solution to reduce the number of unemployed. This positive trend needs to continue to maintain its growth so that the MSME sector on a large scale is able to overcome the unemployment problem in Indonesia. This research was conducted with the aim of determining the role of managerial capabilities and product differentiation on the performance of MSMEs in the city of Batam. The object of this research is MSMEs in Batam Kota sub-district. The total population in this study is 34 MSME actors. The number of samples in this study was calculated using the saturated sample technique, so that the number of samples in this study was 34. The results of the study are known that partially managerial ability has a significant effect on MSME performance, and product differentiation has a significant effect on MSME performance. Simultaneously, managerial ability and product differentiation have a significant effect on product performance From the results of this study, it is expected that MSME actors have managerial abilities in managing MSMEs and have product differentiation from other similar productsKeywords: Managerial ability, product differentiation, MSME performance